JAPANESE WORK CULTURE: IMPLEMENTING 5S AND HORENSO FOR STUDENTS OF STATE VOCATIONAL HIGH SCHOOL 1 BUAHDUA SUMEDANG - Novitasari, Raden; Kuraesin, Uning; Ariestafuri, Nurza; Rahardjo, Hardianto; Tresnasari, Ningrum (LPPM Univ. Ibn Khaldun Bogor, 2025)
As the demand for professional workers of productive age increases due to Japan’s declining population, the number of Indonesian workers sent there has also grown. This condition encourages many educational institutions to prepare their students to be ready to work in Japan after completing their studies. One effort is by providing Japanese language learning at the senior high school and vocational school levels. However, mastery of speaking, writing, listening, and reading alone is not sufficient to enter the Japanese workforce Cultural and work ethic differences remain a major challenge, particularly the understanding of the 5S and HoRenSo principles, which are work principles implemented across almost all companies and industries in Japan. Proper application of these principles plays an important role in ensuring smoother workflows and improving work outcomes. Unfortunately, most Indonesian workers are still unfamiliar with them, so when they begin working in Japan, they require an adaptation period that can reduce efficiency. To address this issue, a cluster of lecturers from the Japanese Language Study Program at Widyatama University collaborated with SMK Negeri 1 Buahdua Sumedang to introduce and train students in 5S and HoRenSo principles for the students there.